Student Entrepreneurial Intention: The Role of Support, Emotional Intelligence, Personal Attitude, and Creativity among Economic Student - Siti Nur Hasanah; Tsabita Khwarazmita (Universitas Muhammadiyah Malang, 2023)
Indonesia still requires more entrepreneurs, predominantly young entrepreneurs who could resolve the problems of unemployment and poverty. This research aims to discover the contribution of support (family and education), personal attitude, emotional intelligence, and creativity in supporting the entrepreneurial intention of students. This type of research is quantitative with a population and sample of 99 after using census sampling techniques. Data collection uses a questionnaire and continues to be tested with the SmartPLS 4.0 analysis tool. Through investigations, research results found that support influences personal attitude, emotional intelligence influences creativity, personal attitude and creativity influence entrepreneurial intention, personal attitude and creativity mediate support, and emotional intelligence influences entrepreneurial intention.